THE ROLE OF INTERNATIONAL ENVIRONMENT FACTORS TO ACHIEVE THE SUCCESS STRATEGIC PLANNING IN ORGANIZATION: A CASE STUDY IN DNO COMPANY – ERBIL - Diyar A. Mustafa Khoshnaw (QALAAI ZANIST JOURNAL, 2021)
The current business field is characterized by high competition. The field is in continuous change as most organizations look for new strategies to achieve a state of leadership and uniqueness in the international market in order to make advances in the competition. Therefore, they look for new methods to enter the markets by minimum costs and to get maximum benefits. The current research aimed to identify the role of international environment factors in achieving success strategy planning in organizations. Through field testing of the views of managers, assistants and heads of departments in a sample of OMV company city in Erbil - Kurdistan, these factors were found to vary in their effects toward the strategic planning dimensions. There has recently been a sudden change in the international business environment as a result of increased competition especially in the economic sector. Also, the field has witnessed variation in the capacity in adoption, and strategic planning is one of the modern models in the conduct of organizations. Therefore, the subject of international environment factors and strategic planning for business has attracted the attention of many researchers and scholars focusing on contemporary themes with a huge impact on the performance of organizations in pursuit of excellence. In the field, a presumptive scheme was developed to indicate the relationship between the variables of the study and adopted a model relationship in one direction. The study was based on a set of assumptions that field-tested on a sample of foreign companies operating in the city of Erbil. A number of basic questions for the study were prepared for 30 administrative leaders (managers and their assistants, and department heads) who answered the questions. The questionnaire of this research was designed to collect data which included several measures derived from previous studies, but were modified and redesigned to align with the requirements of the current research. While operations of statistical analysis of the data was done using the software statistical (SPSS) and a number of statistical indicators were calculated which formed the basis to present and discuss the results of field-based analysis. The study reached a number of conclusions, including: 1. The theoretical sector for research dealing with international environment shows that there is confusion between this concept and the concept of the International Management, especially among writers and researches. 2. The presence of a significant correlation between the independent variables (international environment factors) overall and adopted variable (the success strategy planning) in organizations. The research reached a number of recommendations including: The need to work and focus on the analysis of the factors of international environment. This can be achieved by offering training workshops or through field work in administrative levels. In order to achieve the dimensions of strategic planning in the organizations in the sample companies, focus should be directed to the ability of management of organizations within the international environment to discover opportunities and create value. These can reduce the threats and challenges which prevent achieving the best strategy planning.